2020
DOI: 10.1002/ece3.6921
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and passive environmental DNA approaches outperform established methods for detection of quagga mussels, Dreissena rostriformis bugensis in flowing water

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 74 publications
(122 reference statements)
1
47
0
Order By: Relevance
“…Biodiversity studies increasingly use environmental DNA (eDNA)‐based methods to assess community patterns (Cordier et al, 2020; Dornelas et al, 2019), to discover rare organisms (Jerde et al, 2011), and to detect invasive species (Holman et al, 2019). Comparisons between non‐molecular and eDNA biodiversity surveys have consistently shown that eDNA surveys are highly sensitive and can detect species accurately at a reduced cost (Blackman et al, 2020; Borrell et al, 2017; Deiner et al, 2017). However, rigorous optimization and methodological standardization are necessary to correctly interpret data generated from eDNA surveys (Agersnap et al, 2017; Goldberg et al, 2016; Zinger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodiversity studies increasingly use environmental DNA (eDNA)‐based methods to assess community patterns (Cordier et al, 2020; Dornelas et al, 2019), to discover rare organisms (Jerde et al, 2011), and to detect invasive species (Holman et al, 2019). Comparisons between non‐molecular and eDNA biodiversity surveys have consistently shown that eDNA surveys are highly sensitive and can detect species accurately at a reduced cost (Blackman et al, 2020; Borrell et al, 2017; Deiner et al, 2017). However, rigorous optimization and methodological standardization are necessary to correctly interpret data generated from eDNA surveys (Agersnap et al, 2017; Goldberg et al, 2016; Zinger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An unexplored question is to what extent the results of the above single‐species studies (qPCR‐based) also apply to metabarcoding experiments. Some work has directly compared the sensitivity of qPCR and metabarcoding using non‐specific primers (Blackman et al, 2020; Bylemans et al, 2019; Harper et al, 2018; Simmons et al, 2016; Wood et al, 2019). In all these studies, the qPCR assays were shown to be more sensitive for the detection of the study species.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has identified that NNS can be detected using eDNA metabarcoding [37,39], but these surveys aimed at detecting any NNS rather than a specific set of target taxa. Several studies have identified that general target metabarcoding primers show lower reliability and sensitivity compared to species-specific quantitative PCR assays [95,96]. Additionally, previous work has identified that in some cases different bioinformatic methods carry variable sensitivity [97], although this effect is fairly minimal in this dataset (see electronic supplementary material, note 3).…”
Section: Discussionmentioning
confidence: 89%
“…Previous work has identified that NNS can be detected using eDNA metabarcoding [32, 34], but these surveys aimed at detecting any NNS rather than a specific set of target taxa. Several studies have identified that general target metabarcoding primers show lower reliability and sensitivity compared to species-specific quantitative PCR assays [93, 94]. Additionally, previous work has identified that in some cases different bioinformatic methods carry variable sensitivity [95], although this effect is fairly minimal in this dataset (see Supplementary Note 3).…”
Section: Discussionmentioning
confidence: 86%